Giải các phương trình:
a) \(\frac{2x}{x-1}-\frac{x}{x-2}=\frac{x^2}{\left(x-1\right)\left(x-2\right)}\)
b) \(\frac{1}{x+2}-\frac{6}{x-1}+\frac{8}{\left(x+2\right)\left(x-1\right)}=0\)
c) \(\frac{x+2}{x+3}-\frac{x+1}{x-1}=\frac{4}{\left(x+3\right)\left(x-1\right)}\)
d) \(\frac{x-1}{x+2}-\frac{x+1}{x-2}=\frac{x-3}{4-x^2}\)
Giải phương trình
a) \(\frac{2x}{x-1}-\frac{x}{x-2}=\frac{x^2}{\left(x-1\right)\left(x-2\right)}\left(x\ne1,x\ne2\right)\)
\(\Leftrightarrow\frac{2x\left(x-2\right)-x\left(x-1\right)-x^2}{\left(x-1\right)\left(x-2\right)}=0\)
\(\Rightarrow2x^2-x^2-x^2-4x+x=0\)
\(\Leftrightarrow-3x=0\Leftrightarrow x=0\left(tm\right)\)
KL: Vậy...
b)\(\frac{1}{x+2}-\frac{6}{x-1}+\frac{8}{\left(x+2\right)\left(x-1\right)}=0\left(x\ne-2,x\ne1\right)\)
\(\Leftrightarrow\frac{\left(x-1\right)-6\left(x+2\right)+8}{\left(x+2\right)\left(x-1\right)}=0\)
\(\Rightarrow x-1-6x-12+8=0\)
\(\Leftrightarrow-5x=-7\Leftrightarrow x=\frac{7}{5}\left(tm\right)\)
c) \(\frac{x+2}{x+3}-\frac{x+1}{x-1}=\frac{4}{\left(x+3\right)\left(x-1\right)}\left(x\ne-3,x\ne1\right)\)
\(\Leftrightarrow\frac{\left(x+2\right)\left(x-1\right)-\left(x+1\right)\left(x+3\right)-4}{\left(x+3\right)\left(x-1\right)}=0\)
\(\Rightarrow x^2+x-2-x^2-4x-3-4=0\)
\(\Leftrightarrow-3x=9\Leftrightarrow x=-3\left(ktm\right)\)